2008
DOI: 10.1007/s12013-008-9010-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Effects of Hg2+-induced Changes in Cell Volume

Abstract: Using a microfluidic volume sensor, we studied the dynamic effects of Hg 2+ on hypotonic stressinduced volume changes in CHO cells. A hypotonic challenge to control cells caused them to swell but did not evoke a significant regulatory volume decrease (RVD). Treatment with 100 μM HgCl 2 caused a substantial increase in the steady-state volume following osmotic stress. Continuous hypotonic challenge following a single 10-min exposure to HgCl 2 produced a biphasic volume increase with a steady-state volume 100% l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 55 publications
(88 reference statements)
2
15
0
Order By: Relevance
“…Figure 5d is a graph of time constants obtained from the swelling curves shown in Figure 5a-c. We and others previously found that a high concentration of Hg 2+ (>50 μM) could rapidly alter the permeability of Na + , K + , and Cl - ions, leading to extraordinary water flow across the cell membrane 30,31. Therefore, we optimized the dose of Hg 2+ to minimize the side effect of Hg 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5d is a graph of time constants obtained from the swelling curves shown in Figure 5a-c. We and others previously found that a high concentration of Hg 2+ (>50 μM) could rapidly alter the permeability of Na + , K + , and Cl - ions, leading to extraordinary water flow across the cell membrane 30,31. Therefore, we optimized the dose of Hg 2+ to minimize the side effect of Hg 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Microscope slides were cut to ~22 mm × 13 mm to fit on the sensor chip and cleaned as previously described [21]. MDCK cells (ATCC) were grown to confluence on the slide in a 35 mm Petri dish using Dulbecco’s Modified Eagle’s Medium (DMEM) containing 10% fetal bovine serum and 1% penicillin-streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The chamber was perfused with test solutions, and the cell volume was monitored in real time. The ratio of the volume change to the resting volume was calculated as previously described (18). A fresh cell culture was used for each trace, and the data represent the first challenge since we have found that RVD rapidly disappears with repeated stimulation (3).…”
Section: Methodsmentioning
confidence: 99%